Massive Cerebrospinal Fluid Leak of the Temporal Bone - Giannicola Iannella; Alessandra Manno; Emanuela Pasqualitto; Andrea Ciofalo; Diletta Angeletti; Benedetta Pasquariello; Giuseppe Magliulo (Case Reports in Otolaryngology)
Cerebrospinal fluid (CSF) leakage of the temporal bone region is defined as abnormal communications between the subarachnoidal space and the air-containing spaces of the temporal bone. CSF leak remains one of the most frequent complications after VS surgery. Radiotherapy is considered a predisposing factor for development of temporal bone CSF leak because it may impair dural repair mechanisms, thus causing inadequate dural sealing. The authors describe the case of a 47-year-old man with a massive effusion of CSF which extended from the posterior and lateral skull base to the first cervical vertebrae; this complication appeared after a partial enucleation of a vestibular schwannoma (VS) with subsequent radiation treatment and second operation with total VS resection.